2020
DOI: 10.1590/fst.07119
|View full text |Cite
|
Sign up to set email alerts
|

The control of Maillard reaction in white grape molasses by the method of reducing reactant concentration

Abstract: The aim of this study was to investigate the impact of removing sugar and/or amino groups by applying one ion exchange (Dowex 50Wx8) and two adsorbent (Activated Carbon and Amberlite XAD-16) resins to grape juice in the control of Maillard reaction. Grape juices, a control sample and separately applied with each resin, were concentrated up to 50, 60 and 70 °Bx and stored at three temperatures (50, 65 and 75 °C) for 10 days. HMF accumulation was lower in the grape juices which were treated with Amberlite or act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 34 publications
1
10
0
Order By: Relevance
“…The activation energy for HMF formation ranged from 138 to 169 kJ/mol, indicating that HMF formation is temperature‐dependent. These values are consistent with the findings of many researchers reporting that activation energies in food systems vary between 4 and 630 kJ/mol (Çoklar and Akbulut (2020)). In addition, in studies where the activation energies of HMF formation were calculated, E a values were 158.63 kJ/mol for hard molasses (Tosun, 2004), 29.4 kJ/mol for pineapple juice (Rattanathanalerk et al., 2005) and 124 kJ/mol for peach puree (Garza et al., 1999).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…The activation energy for HMF formation ranged from 138 to 169 kJ/mol, indicating that HMF formation is temperature‐dependent. These values are consistent with the findings of many researchers reporting that activation energies in food systems vary between 4 and 630 kJ/mol (Çoklar and Akbulut (2020)). In addition, in studies where the activation energies of HMF formation were calculated, E a values were 158.63 kJ/mol for hard molasses (Tosun, 2004), 29.4 kJ/mol for pineapple juice (Rattanathanalerk et al., 2005) and 124 kJ/mol for peach puree (Garza et al., 1999).…”
Section: Resultssupporting
confidence: 92%
“…Kuşçu and Bulantekin (2016) reported that the protein content of apple pekmez is significantly lower than that of raw apple juice. In addition, Çoklar and Akbulut (2020) investigated the effect of ion exchangers and activated carbon treatment on grape juice on the protein content of grape pekmez samples and found that activated carbon applications reduced the protein content of pekmez samples compared with the control sample. Our study results were complied with these findings.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The brown-colored pigment formation in foods is caused by the Maillard reactions or caramelization [ 16 ]; therefore, the browning index is generally accepted as an indicator of the Maillard reaction. The brown pigment formation in the microencapsulated powders was evaluated by absorbance measurements at 420 nm and 600 nm, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The browning intensity was measured using a spectrophotometric method with minor modifications [16]. A volume of 5 mL of a mixture consisting of equal volume of acetic acid (2% v/v) and formaldehyde (1% v/v) was added to 0.1 mL of 1 mg/mL of samples and centrifuged for 10 min at 4500× g. The resulting supernatant (5 mL) was mixed with 5 mL of ethanol and the mixture was centrifuged again.…”
Section: Browning Index and Grafting Degree Measurement Of The Powdersmentioning
confidence: 99%